Amniotic membrane applied to burns healing: Pre-clinical study (Research, Society and Development, 2021)
This preclinical study aimed to evaluate the tissue repair process of burns treated with human amniotic membrane (hAM) patches in rats. Twenty-four rats were subjected to superficial burns of partial thickness, and randomly allocated into two groups: Control and Treated Group, subdivided into two experimental periods of 7th and 14th days. The lesions were evaluated by digitalized images (macroscopy) and by the analysis of histological sections stained in H&E to quantify the number of inflammatory cells and fibroblasts present in the different experimental times (histomorphometry). The histomorphometric analyses were performed blindly. Statistical analysis employed Kolmogorov-Smirnov and Mann Whitney tests, with 95% confidence interval at 5% significance level (p